Bruton Tyrosine Kinase Inhibition and Its Role as an Emerging Treatment in Pemphigus - Patsatsi, Aikaterini; Murrell, Dedee F. (Frontiers in Medicine, 2021)
Bruton Tyrosine Kinase (BTK) has a key role in multiple pathways involved in inflammation and autoimmunity. Therefore, BTK has become a new therapeutic target for a group of hematologic and autoimmune disorders. The pharmaceutical industry has invested in the clinical development of BTK inhibitors during the last decade. Ibrutinib, for example, which was the first BTK inhibitor to be used in clinical trials, has two approved indications, mantle cell lymphoma and chronic lymphocytic leukemia, and remains under evaluation for additional indications. Rillzabrutinib (PRN1008) is a new, highly potent and selective inhibitor of BTK. Early studies performed in canine pemphigus demonstrated effectiveness. A proof-of-concept, multicenter, phase 2 trial has recently showed the efficacy and safety of oral rilzabrutinib in pemphigus vulgaris. In this mini review, we present evidence regarding the mechanisms affected by BTK inhibition and the concept of BTK inhibition as an emerging new treatment in pemphigus.